Nationwide surveillance on enteric fever to estimate the disease burden in Bangladesh - Mahmood, Amena (BRAC Univeristy, 2017)
This thesis report is submitted in partial fulfillment of the requirement for the degree of B.Sc in Biotechnology, 2016.